Managing LINUS program in Gombak primary schools: A case study of school heads' awareness, leadership styles and commitment / Siti Rohimah Mahmad Rejad - Mahmad Rejad, Siti Rohimah (2014)
LINUS is an abbreviation o f Literacy and Numeracy Screening. The program has been implemented by the Ministry o f Education (MOE) under the National Key Result Area (NKRA) mandate since 2010 to ensure students master literacy and numeracy. In discovering the implementation o f the LINUS Program, this descriptive-correlational study was intended to seek how school heads influence the success o f LINUS program, thus the variables to be measured were several attributes o f the school heads - awareness, commitment and leadership styles. School heads were selected because they are directly responsible for the main leadership o f the schools. The approach taken in this research was largely quantitative. A lot o f information have been collected within a short period o f time by using quantitative techniques. The questionnaires have been tested through a pilot test involving 20 respondents who had been selected at random among the school heads who were attending courses at Institut Aminuddin Baki (IAB) while the respondents were those who attended meeting at PPD Gombak. All the school heads o f primary schools in Gombak district have been randomly selected as the respondents in this study. The analysis from this study shows that most o f the school heads were committed with the LINUS program based on the check list o f commitment, a moderate awareness o f LINUS program by the school heads in Gombak district and a moderate level o f commitment o f LINUS program by the school heads. Meanwhile for leadership style, the school heads can be marked between the M iddle-of-the-Road and the Team style. Data for school performance shows that 65.2% (43 schools) have achieved the KPI, meanwhile 34.8% (23 schools) did not achieved the KPI. In addition, the data shows that there was a moderate and significant relationship between school heads’ awareness and school heads’ commitment (r = 0.554, p-value = 0.000) and there was no statistically significant association between school heads’ leadership and school performance (%(1) = 1.898, p-value = 0.168). Accordingly, all o f the proposed recommendations can be presented to the Ministry o f Education (MOE) to help school heads, especially in providing appropriate recommendations for the problems involving LINUS program to benefit the students.